Off-label drug use in children and adolescents treated with antidepressants and antipsychotics: results from a prospective multicenter trial - Taurines, Regina; Gerlach, Manfred; Correll, Christoph U.; Plener, Paul L.; Malzahn, Uwe; Heuschmann, Peter; Scherf-Clavel, Maike; Rock, Hans; Briegel, Wolfgang; Fleischhaker, Christian; Häge, Alexander; Hellenschmidt, Tobias; et al. (Child and adolescent psychiatry and mental health, 2025)
Off-label psychopharmacologic medication use is widespread in child and adolescent psychiatry, but little is known about its associated factors. This study aimed to assess frequency and determinants of off-label use of antidepressants and antipsychotics in youths in daily clinical practice.